Bangladesh: A Playground for Big powers - Timalsina, Saroj Kumar (Khwopa Journal, 2025)
The aim of this article is to analyze Bangladesh’s fundamental situation from its founding to the August rebellion of 2024. The author has used a variety of primary and secondary materials for this course, including interviews with different people, scholarly books, the opinions and views of freelancers stated in various print and electronic media, journals, seminar papers, papers presented in various workshops, etc. Because the study is qualitative, the author assessed the data using both descriptive and analytical methods. Bangladesh is a major participant in the Indo-Pacific due to the Rohingya genocide, the maritime boundary disputes between Bangladesh and India and Bangladesh and Myanmar, and its strategic location at the intersection of South and Southeast Asia, which gives it access to the Bay of Bengal. China and Bangladesh now have a stronger strategic alliance because to the BRI, which has promoted trust and collaboration on a number of levels. Mishra (2018) asserted in this line that the Maldives fiasco clearly demonstrated China’s unrelenting territorial expansion. Big powers are also concerned about this issue. All of these achievements were fully realized during Shekh Hasina’s administration, but the civil rebellion that followed her rule was abruptly put down because of geopolitical sensitivity and the great power struggle in the Bay of Bengal. The author contends that because of Bangladesh’s shifting geostrategic importance, academic IR has developed an interest in the nation despite its small size. The report claims that due of Bangladesh’s growing geopolitical importance, major powers are eager to come and aid in its development. Studying IR in Bangladesh is so essential. From the beginning to the present, the author has made every effort to convey the core of Bangladesh’s history.